2006
DOI: 10.1080/09674845.2006.11732733
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a liquid nutritional supplement on viral load and haematological parameters in HIV-positive/AIDS patients

Abstract: The effect of a nutritional supplement on the immune status and haematological parameters of HIV-positive/AIDS patients is tested using standard procedures. This clinical trial of 35 patients consists of a baseline visit and three months of supplementation from April to September 2003. Results showed that viral load decreased significantly (P<0.002) with time following supplementation. Mean cell volume (MCV) and mean cell haemoglobin concentration (MCHC) increased significantly (P<0.002 and P<0.0002, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…In Vyas et al study, the prevalence of Cryptosporidium (37.93%) in northern India and the prevalence of Isospora belli (31.3%) in southern India was more than other species (19). Also, in Akinbo et al study in Nigeria in 2010, Cryptosporidium (22.2%) and Isospora belli (7.8%) species were seen as opportunistic infections (6), which are consistent with the present study and some other studies (20)(21)(22)(23)(24). Mohandas et al (2002) in India showed that 30% of HIVpositive patients were suffering from intestinal parasitic infections, 10.8% of which had Cryptosporidium parvum infection and 8.3% were diagnosed as having Giardia (giardiasis).…”
Section: Discussionsupporting
confidence: 82%
“…In Vyas et al study, the prevalence of Cryptosporidium (37.93%) in northern India and the prevalence of Isospora belli (31.3%) in southern India was more than other species (19). Also, in Akinbo et al study in Nigeria in 2010, Cryptosporidium (22.2%) and Isospora belli (7.8%) species were seen as opportunistic infections (6), which are consistent with the present study and some other studies (20)(21)(22)(23)(24). Mohandas et al (2002) in India showed that 30% of HIVpositive patients were suffering from intestinal parasitic infections, 10.8% of which had Cryptosporidium parvum infection and 8.3% were diagnosed as having Giardia (giardiasis).…”
Section: Discussionsupporting
confidence: 82%
“…Ascaris lumbricoides was the second commonest parasite and the most frequently detected intestinal parasite in HIV patients. Previously, other authors [14,18] also reported A. lumbricoides as a single parasitic infection among HIV patients.…”
Section: Discussionmentioning
confidence: 99%
“…This may also explain the low RDW among HIV patients in this study. There is evidence that nutritional intervention assists in maintainig and optimizing nutritional status and immune function, prevents the development of nutritional deficiency, loss of weight and lean body mass, promotes response to medical treatment and increases longevity in HIVinfected persons (Oguntibeju et al, 2006). Also, nutritional supplementation has been shown to decrease viral load (Bouic et al, 2001;Oguntibeju et al, 2006).…”
Section: Discussionmentioning
confidence: 99%